2014
DOI: 10.1093/fampra/cmu022
|View full text |Cite
|
Sign up to set email alerts
|

The psychometric qualities of the Groningen Frailty Indicator in Romanian community-dwelling old citizens

Abstract: This study showed the GFI to be a feasible and valid instrument to assess frailty in independent-living old Romanians. Compared with the Dutch old, the prevalence of frailty in independently living old Romanians is high. Further research is needed to determine the appropriate cut-off points in the GFI scores in different care systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 23 publications
2
17
0
2
Order By: Relevance
“…This reinforces the expected validity (face validity) and therefore makes it possible to confirm the absence of problems related to translation [19]. The internal consistency generally exceeded the recommended minimum alpha coefficient standard for group comparison of 0.70 [26,29] and also was higher than the reliability of the GFI in Dutch (0.68) [12] and Romanian study (0.746) [30]. Indeed, Ware [29] considered the reliability of 0.5 or above was acceptable.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…This reinforces the expected validity (face validity) and therefore makes it possible to confirm the absence of problems related to translation [19]. The internal consistency generally exceeded the recommended minimum alpha coefficient standard for group comparison of 0.70 [26,29] and also was higher than the reliability of the GFI in Dutch (0.68) [12] and Romanian study (0.746) [30]. Indeed, Ware [29] considered the reliability of 0.5 or above was acceptable.…”
Section: Discussionsupporting
confidence: 67%
“…The mean frailty score (6.77) using the GFI among the elderly in the study was higher than their Dutch [7,12] and Romanian [30] counterparts. Drubbel et al [7] and Peters et al [12] found a mean score of 3.2 (n = 623; mean age 73.4 years) and 4.5 (n = 353, mean age = 81 years), respectively, in community-dwelling older patients in the Netherlands.…”
Section: Discussionmentioning
confidence: 53%
“…Only four studies considered content validity, with three given a positive rating (all from Brazil) . Internal consistency was assessed in three studies, all of which were given an indeterminate rating . Two studies assessed criterion validity, although only one assessed it adequately .…”
Section: Resultsmentioning
confidence: 99%
“…[49][50][51] Internal consistency was assessed in three studies, all of which were given an indeterminate rating. [50][51][52] Two studies assessed criterion validity, although only one assessed it adequately. 52 All but two studies assessed construct validity, 52,53 although it was the only criterion assessed in 12 of these studies.…”
Section: Critical Appraisalmentioning
confidence: 99%
See 1 more Smart Citation